Peran Isteri Dalam Meningkatkan Pendapatan Ekonomi Keluarga (Studi Tentang Asisten Rumah Tangga di Desa Alah Air Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti) - Miftahurrahmah, Miftahurrahmah; Yusuf, Yusmar (Journal of Education Religion Humanities and Multidiciplinary, 2024)
Wives who work outside the home have two roles that must be carried out, namely domestic roles and public roles. The increasing need for the household makes a wife work in the informal sector, because it does not require higher education, does not require special conditions, is not tied to a certain time or agency. One of the types of jobs that do not require higher education is working as a domestic assistant. This study aims to find out how the role of wives in family economic income in Alah Air Village. This study uses qualitative research methods. The theory used is Role Theory. The data in this study was collected through interviews, observations, and documentation. Two techniques for determining subjects, namely deliberately (purposive) and (snowball) are used in this study. The subjects in this study are five domestic assistants. The results of research that have been carried out show that the role of wives who work outside the home as domestic assistants is due to several factors: increasing economic levels and low incomes, and irregular husbands' income because the husband also works in the informal sector such as: barbers, construction workers and freelance day laborers. Their education level, which is only limited to the junior and senior high school level, does not have many options other than working in the informal sector such as becoming a domestic assistant. By working outside the home, the wife has a dual role, but it is not a problem for them the wife can divide the time between being a wife and a mother at home and must work outside the home well. This job is a part-time job that only uses 2-4 hours of working time. The income of the wife working as a domestic assistant can help increase the family's economic income.